Building Inclusive and Sustainable Educational Libraries in Multicultural Schools - Rajaa Younes Al-Abyad (21685750) (2025)
This Poster was presented by Rajaa Younes Al-Abyad. Libraries Lead Forum 2025/Tunisian School in Doha, Qatar (IFLA MENA 2025) This project aims to establish inclusive and sustainable school libraries in environments where students come from diverse cultural and national backgrounds. Its goal is to foster a fair and open educational atmosphere that embraces diversity. These libraries are designed to meet the needs of all students—regardless of their language or cultural background—by providing a wide range of educational resources that reflect and support this diversity, thereby ensuring equal access to knowledge. Such libraries serve as platforms for mutual understanding and positive interaction among students by incorporating content that represents various cultures and minority identities. They also rely on modern technologies and renewable educational resources, ensuring that learning remains current and sustainable. At their core, these libraries contribute to building balanced educational communities that celebrate cultural differences, foster a sense of belonging, and support the development of generations who are more aware, inclusive, and accepting of diversity. Other Information Poster was presented at: Libraries Thriving Together in an Open Ecosystem https://www.qnl.qa/en/libraries-lead-forum-2025 License: https://creativecommons.org/licenses/by/4.0/ Conference information: Libraries Lead Forum 2025 https://www.qnl.qa/en/libraries-lead-forum-2025/agenda